2018
DOI: 10.1136/thoraxjnl-2016-209429
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence estimates and risk factors for early childhood wheeze across Europe: the EuroPrevall birth cohort

Abstract: The prevalence of early childhood wheeze varied considerably across Europe. Lower respiratory tract infections, day care attendance, postnatal smoke exposure and male gender are important risk factors. Further research is needed to identify additional modifiable risk factors that may differ between countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 39 publications
1
26
0
2
Order By: Relevance
“…The sample size was estimated to provide 80% power at a 5% significance level to assess the primary association between an occurrence of at least one wheezing exacerbation within 3 months of the index ED visit and the overall baseline TRACK score, adjusting for patients' sex and atopy, which are known to impact preschool wheeze severity . Based on a previous study we assumed that approximately 40% of participants would have further exacerbations .…”
Section: Methodsmentioning
confidence: 99%
“…The sample size was estimated to provide 80% power at a 5% significance level to assess the primary association between an occurrence of at least one wheezing exacerbation within 3 months of the index ED visit and the overall baseline TRACK score, adjusting for patients' sex and atopy, which are known to impact preschool wheeze severity . Based on a previous study we assumed that approximately 40% of participants would have further exacerbations .…”
Section: Methodsmentioning
confidence: 99%
“…Selby et al ’s study published in  Thorax fills this important gap 12. Although their wheeze measure used does not differentiate any of the early childhood asthma/wheeze phenotypes described to date, their findings on the substantial variation in wheeze prevalence across a number of countries and differential patterns of risk factors provide valuable insights and will inform future research.…”
mentioning
confidence: 99%
“…Lack of delineation of early transient wheeze from other wheeze phenotypes (intermediate-onset or early persistent wheeze) in the EuroPrevall analysis may have influenced the ability to find this association. Another reason Selby et al ’s analysis did not find more previously identified associations could be their approach to model construction, which was more predictive modelling in nature without consideration of potential causal pathways when variables are included in the models, which may lead to underestimates of associations 12. For example, a model including both breast feeding and any potential mediators that lie in the causal pathway between breast feeding and wheeze may mask the association.…”
mentioning
confidence: 99%
See 2 more Smart Citations